Cryptococcus neoformans Infection Induces IL-17 Production by Promoting STAT3 Phosphorylation in CD4+ T Cells - Guo, Xiaoman; Mao, Xinru; Tian, Di; Liao, Yixin; Su, Bintao; Ye, Chaoliang; Shi, Dongling; Liu, Tie Fu; Ling, Yun; Hao, Yi (Frontiers in Immunology, 2022)
Cryptococcus neoformans infection in the central nervous system is a severe infectious disease with poor outcomes and high mortality. It has been estimated that there are 220,000 new cases each year. Over 90% of C. neoformans meningitis cases were diagnosed in AIDS patients with CD4+ T cell count <100 cells/μl; however, the mechanism of cryptococcal meningitis in patients with normal immune functions remains unclear. IL-17 is a pro-inflammatory cytokine and plays an important role in anti-fungal immunity. Here we report that significantly high levels of IL-17 were predominantly detected in the cerebrospinal fluid of patients with either AIDS- or non-AIDS-associated C. neoformans meningitis but not in patients with tuberculous meningitis or non-neurosyphilis. Antifungal therapy minimized the IL-17 level in the cerebrospinal fluid. An in vitro mechanistic study showed that C. neoformans stimulation of healthy peripheral blood mononuclear cells prompted IL-17 production, and CD4+ T cells were the predominant IL-17-producing cells. IL-17 production by C. neoformans stimulation was STAT3 signaling dependent. Inhibition of STAT3 phosphorylation attenuated the C. neoformans-mediated IL-17 expression. Our data highlighted the significance of CD4+ T cells in antifungal immunity and suggested IL-17 as a diagnostic biomarker of C. neoformans infection and STAT3 as a checkpoint for antifungal targeted therapies.